Simulation study on the effect of ignition location on pressure piling - Nur Fatin Najwa, Kamaruddin (2014)
An explosion of flammable mixtures in interconnected compartments is commonly defined as pressure piling. Piling pressure is phenomenon when the peak pressure observed is higher than the predictable thermodynamic values. The two main mechanisms affecting pressure piling are pre-compression and violence of explosion. Therefore, this paper is aim study on the effect of ignition location on pressure piling using Computational Fluid Dynamic (CFD) simulation. Different points of ignition were studied using this simulation which are central and end point in the interconnected vessel (primary vessel).Besides that the role played by pre-compression and violence of explosion were also studied. In this studied, CFD codes were used as this simulation able to reproduce the explosion phenomenon (propane air) strongly depends on the sub-models used for turbulence and combustion. The proportion of the propane air used was 50-50 .The model of the interconnected vessel were construct in the Gambit with the height and width of the primary vessel are 0.75cm and 0.305.Meanwhile the height and width of the secondary vessel are 0.15cm and 0.26cm.Later on, the model was imported to the Fluent to reproduce the explosion. From my research, the peak pressure for ignition location at the end in the primary vessel gives the highest value than the peak pressure of central ignition location. This is due to the end ignition location; the flame has much more time to develop turbulence before it enters the secondary vessel. This method is the best to study about an explosion in interconnected vessel because of low cost involve rather than sacrifice a plant which is something irrational to be done. From this study we can clearly see that the end ignition location produced higher peak pressure than the central ignition location due to the development of the turbulence intensity